2008
DOI: 10.1016/j.amepre.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Sun Protection in Winter Outdoor Recreation

Abstract: Background-Unprotected and excessive exposure to ultraviolet radiation (UVR) is the primary risk factor for skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Another study on ski area employees found reduction in sunburns by employees immediately [42] although this reduction was no longer evident in the following summer [4] or when the intervention was distributed throughout the North American ski industry [4]. Finally, the sun protection program at ski areas did not affect sunburn prevalence among guests [237].…”
Section: Interventions In Occupational Settingsmentioning
confidence: 98%
“…Another study on ski area employees found reduction in sunburns by employees immediately [42] although this reduction was no longer evident in the following summer [4] or when the intervention was distributed throughout the North American ski industry [4]. Finally, the sun protection program at ski areas did not affect sunburn prevalence among guests [237].…”
Section: Interventions In Occupational Settingsmentioning
confidence: 98%
“…Prior findings show that people living at higher altitude near ski areas are most aware of the dangers of UV. 56,57 Thus, it is unlikely that the factors associated with SSW practices would change in other states. Nonetheless, data from other states are needed to corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting strategies involve developing cancer communication messages geared for specific groups that may be most in need, or most receptive, to the message (Walkosz, Buller, Andersen, Scott, Dignan, et al, 2008). In contrast, tailoring strategies involve interventions created specifically for individuals based on unique characteristics, such as cancer risk status or readiness for change, have been developed and proven efficacious using print materials, telephone, and individualized web-based channels of communication Personal Cancer Communication 19 (Gil, Mishel, Belyea, Germino, Porter, et al, 2007;Latimer, Salovey, & Rothman, 2007;Mishel, Germino, Gil, Belyea, Laney, et al, 2005;Mooney, Beck, Friedman, & Farzanfar, 2002;Naor, Benac, & Harris, 2007).…”
Section: What Are the Most Important Directions Of Research In This Amentioning
confidence: 99%